Experience with the use of Stimol® in Acute Pyelonephritis in Children - G.Yu. Zvenigorodska; G.S. Guminska; M.M. Demchenko; O.B. Pedosenko; L.A. Shangutova; Yu.O. Kyslova; A.P. Konoplitska (Zaslavsky O.Yu., 2013)
The results of the clinical use of Stimol® in the comprehensive treatment of acute pyelonephritis in 58 children. It is established that the inclusion of metabolism corrector Stimol® in complex of medical treatment of patients with acute pyelonephritis contributes to the stabilization of the clinical condition of patients, reducing symptoms of intoxication (improved appetite, reduced general malaise, normalization of temperature). The findings show the feasibility and clinical efficacy of Stimol® administration, which can be regarded as one of the promising methods of detoxification therapy.